Seneka, Apocolocyntosis 1–4 „Śmierć Boskiego Klaudiusza” - Berger, Łukasz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
The paper consists of a new Polish translation of the initial part of Apocolocyntosis (1–4) by Seneca the Younger with a short introduction, notes and a commentary.